2015
DOI: 10.2217/pgs.15.121
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Drug-Responsive Regulatory Elements

Abstract: Nucleotide changes in gene regulatory elements can have a major effect on interindividual differences in drug response. For example, by reviewing all published pharmacogenomic genome-wide association studies, we show here that 96.4% of the associated single nucleotide polymorphisms reside in noncoding regions. We discuss how sequencing technologies are improving our ability to identify drug response-associated regulatory elements genome-wide and to annotate nucleotide variants within them. We highlight specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Enhancers have been identified as potential determinants of drug response [53,54]. Here, we used ChIP-seq for H3K27ac to identify metformin-responsive associated enhancers and found putative enhancer sequences near genes related to metformin action on gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancers have been identified as potential determinants of drug response [53,54]. Here, we used ChIP-seq for H3K27ac to identify metformin-responsive associated enhancers and found putative enhancer sequences near genes related to metformin action on gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We expect that epigenomics research focused on the regulatory role of GWAS associated SNPs located in non-coding regions might provide a deeper understanding of pathways involved in the response to antihypertensive drugs. Notably, more than 96% of the associated SNPs from GWAS in pharmacogenomics reside in non-coding regions, which suggest these common variants are regulatory ( Luizon and Ahituv, 2015 ). In addition, gene–gene interactions among common regulatory variants can have strong effects in drug response phenotypes ( Sadee et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gene–gene interactions among common regulatory variants can have strong effects in drug response phenotypes ( Sadee et al, 2014 ). Notably, findings from 108 GWAS in pharmacogenomics revealed that 96.4% of the 928 associated single nucleotide polymorphisms (SNPs) are located in non-coding regions ( Luizon and Ahituv, 2015 ). These findings suggest that most of common variants associated with variability in drug response are regulatory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to human disease, genetic variation in gene regulatory elements can have a significant effect on drug response. Notably, 96.4% of genetic polymorphisms identified in GWAS of pharmacogenomic traits were in non-coding regions 6 . High-throughput and massively parallel methods were described to decode and characterize the impact of these variants 7 .…”
Section: Functional Studies In Pharmacogenomics (Wang Ahituv)mentioning
confidence: 99%